Comparação entre centrifugação e microfiltração na clarificação do suco tropical de maracujá - Oliveira, Ricardo Cardoso de (2008)
The value of passion fruits is not only because the nutritional characteristics, but also for its intense particular flavor and its high acidity, which make it an interesting strong base for fruit juice drink manufacture. Moreover, the main species are good sources of vitamin A and the niacine. Its flavor in spite of being so excellent tends to be superintend. The microfiltration is a feasible process that allows the clarification and the refinement occur in single step, thus reducing the time and cost the process and producing a juice of superior quality. However, this process presents problems with regard to the decline of flow of permeated in function of the processing time, being this decline associated to phenomena of fouling. Seeking for an alternative to the process of clarification of the tropical juice of passion fruit, it was studied and compared in this work the microfiltration and the centrifugation of the tropical juice of passion fruit. The influence of the operational conditions, transmembrana pressure and enzymatic concentration, had been studied in the process of clarification using the microfiltration. The tropical passion fruit juice were treated with 100 and 200 ppm of enzyme and then microfiltered. Two ceramic membranes having 0.3 and 0.8 um pore size were tested in these microfiltration using 1.0 and 3.0 bar transmembrane pressures. The quality of microfiltered juice was compared to that of a juice centrifuged during half hour at 3500 rpm. The best condition of microfiltration was chosen based on higher permeated flow and best physical-chemical quality. The microfiltration condition that resulted in a juice of good quality was with the membrane of 0.3 um pore size operated the 1.0 bar. This condition was obtained with a juice previously treated with 100 ppm of enzyme. Under these conditions it was achieved the permeate flow of 56 kg h-1 m-2 and 100% removal of solid in suspension and 97% reduction of turbidity in the permeate. In addition it was observed a decline of permeate flux due to the fouling. The variation of the transmembrana pressure and the enzymatic concentration did not cause significant variation in pH and density, but reductions were observed in the content of soluble solids, total solids and both total and reduced sugars, being some of theses reductions above 10%. The centrifugation process reduced more than 97% of the turbidity and of the content of suspended solids, for both the enzymatic treatments. The others parameters evaluated in the centrifuged juice showed a similar behavior as those observed for the microfiltered juice.